If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 5)(3x + 2) = 0 Reorder the terms: (5 + 2x)(3x + 2) = 0 Reorder the terms: (5 + 2x)(2 + 3x) = 0 Multiply (5 + 2x) * (2 + 3x) (5(2 + 3x) + 2x * (2 + 3x)) = 0 ((2 * 5 + 3x * 5) + 2x * (2 + 3x)) = 0 ((10 + 15x) + 2x * (2 + 3x)) = 0 (10 + 15x + (2 * 2x + 3x * 2x)) = 0 (10 + 15x + (4x + 6x2)) = 0 Combine like terms: 15x + 4x = 19x (10 + 19x + 6x2) = 0 Solving 10 + 19x + 6x2 = 0 Solving for variable 'x'. Factor a trinomial. (5 + 2x)(2 + 3x) = 0Subproblem 1
Set the factor '(5 + 2x)' equal to zero and attempt to solve: Simplifying 5 + 2x = 0 Solving 5 + 2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 2x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 2x = 0 + -5 2x = 0 + -5 Combine like terms: 0 + -5 = -5 2x = -5 Divide each side by '2'. x = -2.5 Simplifying x = -2.5Subproblem 2
Set the factor '(2 + 3x)' equal to zero and attempt to solve: Simplifying 2 + 3x = 0 Solving 2 + 3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 3x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 3x = 0 + -2 3x = 0 + -2 Combine like terms: 0 + -2 = -2 3x = -2 Divide each side by '3'. x = -0.6666666667 Simplifying x = -0.6666666667Solution
x = {-2.5, -0.6666666667}
| -78+7x=114-5x | | 5p^2+10p-40=0 | | 8y+43-74=-15 | | 3/4x-1/8x=6+1/8x | | -78+7x=-4x+154 | | 6x+2(4x+18)=162 | | 3.5x-1=-1/2 | | [7m+4]=1 | | 2(x+3)=-20 | | 2w+18=34 | | 9(8-3x)=3(6+a) | | 7x+5=-115-5x | | 0=9(k-.67)+33 | | 0=X^3+7x^2-x-7 | | 24x=-9x^2+5 | | 108=7x+3(2x-3) | | (2/3)x=14 | | 9a+9+7a+9= | | 81/33=X/5.5 | | 0=x^3+7x-x-7 | | 2x+4=-6x-4 | | 56=2x+4(4x-13) | | 14/x=2/5 | | 2y*2+12y+10=0 | | -115/6-21/9 | | 0=12m^2n^2-8mn+1 | | 8/x=14/8 | | 15=32-6 | | 3(8-2w)=-2x-6 | | b/-16=-7 | | 9+3x=x+9 | | 2(a-8)+7=5(a+2)-4a-19 |